Penguatan Sistem Sertipikat Elektronik sebagai Upaya Preventif Meningkatkan Sekuritas Pertanahan Nasional - Nurfajrina Radhwa, Jihan (Lembaga Teewan Journal Solutions, 2026)
This study aims to provide an explanation of the urgency or necessity of strengthening the electronic certificate system and the form of strengthening the electronic certificate system as a preventive measure to improve national land security. The technological transition has legal implications as well as challenges for electronic certificate security. Responsive regulations are key to ensuring legal certainty and legal protection through strengthening the electronic certificate system. This research is normative with a statutory and conceptual approach. The results of the study indicate the urgency of strengthening the electronic certificate system as a preventive measure to improve national land security due to the ongoing problems of converting conventional land certificates to electronic land certificates, as well as various implementation problems such as the unavailability of monitoring mechanisms, socialization, and assistance for the transition from conventional certificates to electronic certificates. Meanwhile, the form of strengthening the electronic certificate system as a preventive measure to improve national land security includes efforts to strengthen control mechanisms through the formulation of technical instructions for electronic certificate conversion, efforts to strengthen the implementing structure through empowering the quality and competence of implementers, and efforts to strengthen socio-cultural aspects through comprehensive socialization and assistance.